Childhood Poverty and Labour Market Exclusion. Findings from a Swedish Birth Cohort - Bäckman, Olof
Research has consistently shown that poverty and economic hardship have negative consequences for children. Few studies, however, have examined whether these consequences persists into adulthood. In the present paper we broaden the focus and analyse how living conditions during childhood and adolescence structure socio-economic circumstances also in midlife. How does exposure to poverty during childhood and adolescence affect future probabilities for labour market exclusion and inclusion in early adulthood and in midlife? The data are drawn from a new longitudinal Swedish data set – the Stockholm Birth Cohort Study (SBC) – in which we can follow a cohort of Swedes from birth (1953) to the age of 48 (2001). Our results show that childhood poverty clearly has a negative impact on attainment in adulthood. Persistent poverty in the family of origin and entering poverty in adolescence are particularly detrimental for life chances. This is most salient in the analysis of exclusion in midlife. Educational achievement and deviant behaviour (criminality and drug abuse) are identified as important intervening variables. The results are interpreted as a process of cumulative disadvantage. In our final analyses we focus on those excluded from the labour market in early adulthood and their likelihood to be included in midlife. We find that resource attainment in terms of education and family has positive effects for the chance for inclusion and may in that respect be regarded as turning points.childhood poverty; socio-economic circumstances; labour market exclusion